Testing Various Liquid Organic Fertilizers and Varieties for Yardlong Bean (Vigna unguiculata L.) on Limited Land in Pengempon Village, Sruweng, Kebumen - Fauziyatul Fitri; Rennanti Lunnadiyah Aprilia (Asosiasi Dosen Muda Indonesia, 2026)
Limited agricultural land and the increasing volume of biodegradable household waste require cultivation technologies that are efficient, sustainable, and applicable to small-scale vegetable production. Liquid organic fertilizer (LOF) produced from fruit and vegetable waste has the potential to recycle organic materials while supplying nutrients for crop growth. Objective: This study aimed to evaluate the growth and yield responses of three yardlong bean varieties to different sources of waste-derived LOF under limited-land polybag cultivation. Methods: A quantitative experimental approach was employed using a 4 × 3 factorial Randomized Complete Block Design with three replications. The first factor consisted of four LOF treatments: no LOF, fruit-waste LOF, vegetable-waste LOF, and mixed fruit–vegetable waste LOF. The second factor comprised the Parade, Fantastik, and Komet varieties. Plant height, leaf number, pod number, and pod weight were measured directly. The data were analyzed using factorial analysis of variance, followed by Duncan’s Multiple Range Test at the 5% significance level when significant differences were detected. Results: LOF application significantly supported early vegetative growth, particularly by increasing the number of leaves at two weeks after planting. Fruit-waste LOF produced the numerically highest leaf number, although its effect was statistically comparable to vegetable-waste and mixed fruit–vegetable waste LOFs. No marked differences were detected among the three varieties, while plant height and yield components showed relatively uniform responses during the first three harvests. Implications: Household fruit and vegetable waste can potentially be processed into an alternative fertilizer input to support the early establishment of yardlong bean in limited-land cultivation. Optimization of LOF concentration, application frequency, and nutrient composition is required to improve its contribution to pod production. Originality: The originality of this study lies in the simultaneous comparison of three waste-derived LOF sources and three yardlong bean varieties within a factorial polybag experiment under limited-land conditions.